Optoelectronic methods for detecting air objects and measuring their coordinates - Карташов, В.М.; Корытцев, И.В.; Шейко, С.А.; Олейников, В.Н.; Зубков, О.В.; Бабкин, С.И. (Radiotekhnika, 2020)
The analysis of optical-electronic methods (OEM) is carried out in order to select and study an OEM capable of solving the problems of detecting and determining the coordinates of small unmanned aerial vehicles. With this aim in view, various OEM measurements of distance to objects are considered. Optoelectronic methods (OEM) in the measurement modes are characterized by high accuracy, which leads to their successful integration with electronic complexes for various purposes. The authors proposed to classify the OEM according to the physical principle into two large groups: active and passive OEM for measuring range. Interference and modulation methods are evaluated. The considered active methods are highly accurate, but require significant energy consumption and do not provide secrecy of work. Passive OEM range measurements are considered in more depth. The OEM with matrix sensors are subdivided into single-chamber and stereoscopic. Methods, that do not require the participation of the human visual apparatus in taking measurement readings and provide complete automation of decision-making, are of particular interest. The considered photosensitive sensors that detect air objects, both day and night, have a matrix structure and can be integrated into a single optoelectronic system for detecting and measuring range. The advantage of the matrix OEM is the ability to use simultaneously all three sensors for day, night and thermal vision, which will allow reliable detection, recognition and measurement of coordinates of small air objects.